In-line measurement and modeling of temperature, pressure, and blowing agent dependent viscosity of polymer melts - Schaible Tobias; Bonten Christian (Applied Rheology, 2022)
During processing and bubble growth processes, the melt viscosity changes with temperature, pressure, and blowing agent concentration. Therefore, measurement and prediction methods for viscosity characterization in terms of temperature, pressure, and blowing agent dependency are needed. This study demonstrates the applicability of in-line viscosity measurements during the foam injection molding process and a model for viscosity superposition and prediction. In the present study, polystyrene and a modified polylactide for foaming applications with nitrogen as blowing agent are investigated. By changing the injection speed, temperature, and blowing agent concentration, the process conditions are varied, and thus the resulting pressure drops within the in-line measurement die. The calculated shear rates and viscosities are shifted to a master curve by the application of superposition principles. The viscosity dependency on temperature is described by the Arrhenius equation, the pressure by the Barus equation, and for the blowing agent concentration, a novel Barus-like equation was derived and applied. The prediction of the master curve viscosity function was achieved by the power-law model in combination with the superposition principles and showed good agreement with the shifted in-line data. Finally, the in-line measurements and viscosity predictions are validated by comparing them to rotational and capillary rheometer measurements.